2007
DOI: 10.1002/j.2168-9830.2007.tb00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Learner Achievement and Attitudes under Different Paces of Transitioning to Independent Problem Solving

Abstract: This study examined the effect of the pace of transitioning from worked examples to independent problem solving for students with three different levels of prior knowledge. Three paces of transitioning were examined: immediate transitioning, fast fading, and slow fading. The study was conducted with engineering college freshmen in the engineering knowledge domain of introductory electrical circuit analysis and found a significant interaction between the particpants' prior knowledge and the pace of transitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…It appears to be an instance of the expertise reversal effect described by Kalyuga et al (2003). Reisslein and her colleagues have encountered this effect in two recent engineering-related studies involving high-priorknowledge students who scored much lower on the posttest under conditions in which they received more instruction and practice than under conditions in which they received less instruction and practice (Reisslein et al 2006(Reisslein et al , 2007.…”
Section: Achievementmentioning
confidence: 81%
See 1 more Smart Citation
“…It appears to be an instance of the expertise reversal effect described by Kalyuga et al (2003). Reisslein and her colleagues have encountered this effect in two recent engineering-related studies involving high-priorknowledge students who scored much lower on the posttest under conditions in which they received more instruction and practice than under conditions in which they received less instruction and practice (Reisslein et al 2006(Reisslein et al , 2007.…”
Section: Achievementmentioning
confidence: 81%
“…They found that scores on a test of mental ability accounted for more than 40% of the variance on the increase in achievement from pretest to posttest. Reisslein et al (2007) found that engineering students with high prior knowledge of basic electrical circuits performed better on retention tasks under a fast rate of transitioning to independent problem solving, and that those with low prior knowledge performed better under a slow rate of transitioning. This is consistent with the reports of researchers who have suggested that learner control would be a greater benefit to learners with higher levels of prior knowledge or ability (Corbalan et al 2006;Lawless and Brown 1997;Merrill 2002).…”
mentioning
confidence: 95%
“…In her doctoral dissertation, Reisslein (2005) examined the effect of the pace of transitioning from worked examples to independent problem solving for learners with different levels of prior knowledge in electrical circuit analysis (engineering college freshmen). Under the immediate transitioning condition, learners started practicing problems immediately after the introduction.…”
Section: Expertise Reversal For Instructional Guidance and Sequencingmentioning
confidence: 99%
“…The findings of this study showed that BF resulted in significantly lower near-transfer performance for high prior-knowledge learners compared to EP. In the second study, the researchers examined the retention effects of using three different backward fading speeds (i.e., slow, fast, no fading) for learners with three different levels of prior knowledge (Reisslein, Sullivan, and Reisslein, 2007). The results indicated that the high prior-knowledge participants performed best under the fast and no fading conditions whereas the low prior knowledge participants performed best under the slow fading condition.…”
Section: Introductionmentioning
confidence: 99%